Art and propaganda in the twentieth century : the political image in the age of mass culture - Clark, Toby, 1963- (London : Weidenfeld and Nicolson, 1997)
Revolution and reform, 1900-1939 - Campaign for women's rights - Fascism - Propaganda in the communist states - Propaganda in war - Feminism - Propaganda against propaganda - War in Vietnam - AIDS and propaganda.
Revolution, reform, and modernity, 1900-1939 -- Art, propaganda, and fascism -- Propaganda in the communist state -- Propaganda at war -- The art of protest: from Vietnam to AIDS.
Includes bibliographical references (pages 166-167) and index.
Keywords: 1900-1999; Geschichte 1900-1991.; Politics in art; Propaganda in art; Arts, Modern -- 20th century; Mass media and the arts; Arts, Modern